Bailouts, Bonuses, and the Return of Unjust Gains - Tracy A. Thomas (Washington University Law Review, 2009)
In March 2009, ailing insurance giant American International Group (AIG) triggered a national outcry when it paid out $165 million in government bailout funds for employee bonus incentives. President Obama called the bonus payments an "outrage" and promised that his administration would "pursue every single legal avenue to block these bonuses and make the taxpayers whole." He chastised the firm for its audacity of using borrowed taxpayer monies to reward financial recklessness and greed. This was the same company, of course, who within days of receiving its first infusion of government cash in September 2008, sent its executives on a half-million dollar boondoggle retreat at a fancy desert spa. And just several months after the initial fiasco, AIG tried to award $265 million in further bonuses, adding to performance bonuses of $454 million paid to employees and executives in 2008. It was just over a year ago when AIG turned to the government for its survival. The government stepped in to assist AIG when the company faced imminent death from its risky financial derivative products that were backed by precarious mortgages. Fearful that the toppling giant would trigger a cataclysmic domino effect, the government authorized the bailout funds to keep AIG, and the entire U.S. financial sector, afloat. The question remains whether existing legal avenues are available to curtail the continued bilking of taxpayer funds. A good solution might have been to revise the terms of the loan to prohibit payments of bonuses. This reformation type of remedy would have rewritten the original deal to restrict the use of bailout funds for bonuses or executive payments. However, reformation requires an original meeting of the minds in agreement on the terms, which was mistakenly omitted from the written contract. Here, there was no mistake. The agreement between AIG and the government contained no restrictions on the use of the funds. Thus reformation and other more typical contract remedies like damages are unavailable here in the absence of a breach by AIG. One possible answer lies with the remedy of restitution. Restitution, based on unjust enrichment, is a remedy directed at the defendant that requires the wrongdoer to return all ill-gotten gains. The goal is to return the defendant to the position it would have been in but for the wrongdoing, and prevent it from profiting at the plaintiff‘s expense. While some might consider the idea of an unjust enrichment remedy a "hail Mary" pass, this long shot provides a good analytical foundation to funnel the public outrage towards a legal resolution based on justice.
Keywords: Restitution; Rescission (Law); Financial crises; Bonus system; Unjust enrichment; American International Group Inc.; Troubled Asset Relief Program (U.S.); United States. Emergency Economic Stabilization Act of 2008